The Importance of Paradigm in Understanding the Foundations of Curriculum - Subkhan, Edi (Indonesian Journal of Curriculum and Educational Technology Studies, 2021)
Studying curriculum is challenging, especially for the undergraduate students. Moreover, in Indonesian context, in which curriculum is underdeveloped as a discipline or field of studies, looking for the comprehensive book to encounter the students to comprehend the broad range of curriculum as a field of studies and practice of policy making is difficult. According to my experience as lecturer who teach curriculum theory for undergraduate students, I found that most local publications on curriculum were lack of foundational explanation. Of course, this situation disadvantaging the students, because to be curriculum experts or practitioners, they need comprehensive understanding about the very foundation of the curriculum as a field of studies and policy making practices. Through this book review I propose the work of Ornstein and Hunkins (2018) as one of the must-read books for the novice students who eager to study curriculum. Their work encompassing many topics, ranging from its foundations, theories, practices, and current issues of the curriculum. This magnificent book divided into three parts. First part focusing on the foundations of curriculum, such as its philosophical, historical, psychological, and social foundations. Second part elucidating several principles of curriculum, for instances about curriculum design, curriculum development, curriculum implementation, and curriculum evaluation principles. Third part discussing the current issues on curriculum, especially in terms of international relation and unstoppable move of the globalization.